Proceedings of the 11th World congress on pain : 2005 : Sydney, Australia (IASP Press, 2006)
This overview of selected pain topics, selected from contributions to the 11th World Congress on Pain held August 21-26, 2005, in Sydney, Australia, addresses important developments in both basic research and clinical studies. Contributors to this volume are leaders in the international pain community who strive not merely to reduce pain, but also to maximize quality of life and functionality for each patient.
Keywords: bolest; neurologie; Pain